6p + 11q + 4
Chat with our AI personalities
2p + 3q = 13, 5p - 4q = -2 Multiply the first equation by 4 and the second by 3 and add them, which gets rid of the q: 8p + 15p = 52 - 6, and 23p = 46, so p=2. Plug that into the first equation to find q: 4 + 3q = 13, so q=3. Test your answers in the second equation to be sure: 5(2) - 4(3) = 10-12 = -2. It checks. So p=2, q=3.
q - 9q = -8q
log2 sqrt(q) = p/2 log2 8q = 3 + p And it is root, not route.
36.75
We can not provide a specific value as an answer to this question as both p and q are variables and their value is unspecified.However we can write this as:-8(p + q).We can multiply out the bracket to get:-8p + -8q.This is as far as we can answer this question unless the values of p and q are known.-8(p + q) = -8p + -8q